EFEKTIVITAS PEMBERIAN BAKTERI Bacillus polymyxa MELALUI PAKAN TERHADAP IMUNITAS NON SPESIFIK UDANG VANNAMEI (Litopenaeus vannamei) - Kurniawan, Muhammad Haris; Putri, Berta; Elisdiana, Yeni (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
The addition of Bacillus polymyxa bacteria in the feed as immunostimulant is one of the efforts of disease prevention on vannamei shrimp (Litopenaeus vannamei). The aimed of this research was to know the effectivity of the use of Bacillus polymyxa bacteria in feed towards the non-specific imunity of vannamei shrimp. This research consisted of 4 treatments namely feed with the density of Bacillus polymyxa bacteria 0 cell/ml as control (A), 104 cell/ml (B), 106 cell/ml (C) and 108 cell/ml (D) and each treatment is repeated 3 times. This research has been done in 15 days. Parameters that observed this research were total haemocyte count (THC), phagocytosis activity, differential haemocyte count (DHC) and water quality. The results showed that the addition Bacillus polymyxa bacteria of 106 cell/ml was able to improve THC value 6,6x107 cell/ml on the day 10. The DHC value was in the normal range which is hyalin cell was 52-89% and granular cell was 11-48%. The quality of water maintenance media during this research was in the normal range there were temperature 27,2-28,1Â°C, DO 3,70-3,91ppm, pH 3,70-3,91, and salinity 30-35 ppt.